Analisis Pemberian Makanan Tambahan Terhadap Perubahan Berat Badan dan LILA Pada Ibu Hamil KEK di Wilayah Kerja PUskesmas Kemurang Wetan - Nurjanah, Nana; Wahyani, Anggray Duvita; Rahmawati, Yuniarti Dewi (Universitas Muhadi Setiabudi, 2025)
Backgroud: Pregnant women with nutritional and health problems impact the health and safety of both the mother and the baby, as well as the quality of the baby born. The condition of pregnant women with KEK is at risk of reducing muscle strength that helps the birth process, which can result in fetal death (miscarriage), premature birth, birth defects, Low Birth Weight (LBW) and even infant death. Pregnant women with KEK can interfere with fetal growth and development, namely physical growth (stunting), brain and metabolism, which can cause non-communicable diseases in adulthood. The prevalence of KEK pregnant women in the Kemurang Wetan Community Health Center area is higher at 18.67% compared to the district level prevalence of only 11.94%. Therefore, in 2024 to improve the nutritional status of pregnant women with KEK, a program will be implemented to provide PMT to pregnant women. Objective: To analyze the provision of additional food on changes in body weight and LILA of KEK pregnant women in the Kemurang Wetan Community Health Center work area. Methods:This study used a descriptive analytical study with a cohort design. Descriptive analytical research analyzes the relationship between independent and dependent variables. Researchers analyzed the provision of supplementary feeding with changes in body weight and MUAC in pregnant women with chronic energy deficiency (CED) in the Kemurang Wetan Community Health Center working area using primary data. The study sample consisted of all pregnant women with CED in the first and second trimesters in February 2025. The results: In the body weight variable before and after PMT, the p value was obtained = 0.00, p <α with a paired t-test, meaning Ha was accepted. And in the LILA variable before and after PMT, the p value was obtained = 0.00, p <α with the Wilcoxon test, so Ha was also accepted. Conclusion: There is a difference between the body weight and LILA of KEK pregnant women before and after giving additional food. Key Word: Supplemental feeding, Chronic Energy Deficiency, Body weight, LILA